Re-purposing of marine algae as nitric oxide delivery platforms and the effects on angiogenesis - Ong, Melissa Yu Lin (2019)
Synthetic mesoporous silica is a versatile and popular material widely utilized in drug delivery. Although, synthetic mesoporous silica are able to be synthesized with various morphologies, sizes and properties that can be altered for various applications, their synthesis is not only expensive and time-consuming but it also requires the usage of high energy and toxic materials. The production of synthetic mesoporous silica at a large-scale is not sustainable and commercially feasible. Therefore in order to address these disadvantages, there is a need to explore alternative silica porous materials as a suitable delivery platform. In this project, we studied the usage of natural silica-based porous material derived from diatoms known as diatomaceous earth (DE) as a delivery platform for nitric oxide (NO).